Mount Pleasant, Dorset Excavations 1970-1971 - Wainwright, G. J. (Reports of the Research Committee of the Society of Antiquaries of London, 1979)
This is an account of the excavations at Mount Pleasant, Dorset, in southern England, undertaken in 1970 to 1971. Included are descriptions of human remains and artefacts such as pottery, coins, weaponry and metalwork, together with an account of the methodology used to unearth these.